Evaluation of peri-implant condition in periodontally compromised patients - Guilherme Da Rocha Scalzer Lopes; Alfredo Carlos Rodrigues Feitosa; Fabricia Ferreira Suaid; Jefferson David Melo De Matos; John Eversong Lucena De Vasconcelos; Sergio Lins De Azevedo Vaz; Valdir Cabral Andrade; Renato Sussumu Nishioka; Selva Maria Gonçalves Guerra (Wolters Kluwer Medknow Publications, 2019)
Aims: The aim of the study is to evaluate the profile of peri-implant tissues in periodontally compromised patients. Settings and Design: In vivo - cross sectional study design. Materials and Methods: Fifty-eight implants were evaluated, clinically and radiographically, installed in seven individuals treated by the same team of professionals, during the years 1997 and 2005 in a private dental clinic in Vitória, ES, Brazil; that time of data collection, all implants were at least 10 years of functional loading. The variables related to the dental implants evaluated were: visible Plaque Index, Gingival Bleeding Index (GBI), probing pocket depth, bleeding on probing, and bone level, to relate them to the classification of dental implants. Statistical Analysis Used: The Chi-square and Kruskal-Wallis test were adopted. Results: The total of 58 implants were classified: 11 (18.9%) as healthy and 12 (20.7%) as clinically stable. The other 35 implants (60.4%) had some type of peri-implant inflammation, 20 of them (34.5%) were diagnosed with peri-implant mucositis and 15 (25.9%) with peri-implantitis. Among the variables studied, the results showed statistically significant differences for implant location (P = 0.001) and GBI (P = 0.03). Most of the maxillary implants (85.7%) were classified for some type of peri-implant disease. For the implants which resulted in Score 1 for GBI, most of them (75.0%) were also classified for some type of peri-implant disease. Conclusions: Dental implants placed in periodontally compromised patients may have high long-term survival rates. However, most implants were classified with some type of peri-implant inflammation.